FINANCIAL LITERACY AND RISK PROFILE: AN EXTENSIVE OBSERVATION ON BANK EMPLOYEES - Damayanti, Sylviana Maya; Wicaksana, Pramudya (Jurnal Aplikasi Manajemen, 2021)
People with a high level of financial literacy tend to have better financial management skills to realize their financial well-being through effective financial decisions including investing according to their risk profile. The banking industry is an industry that has the highest inclusive level selected because it can represent financial literacy conditions. On the other hand, the gap between financial inclusion and financial literacy leads to a large number of investment (illegal) cases and complaints to regulators. The purpose of this research is to find out the level of financial literacy and type of risk profile, factors that affect it with bank employees in Bandung as research objects. The sampling technique used is a non-probability sampling technique that is purposive sampling with a total of 408 respondents. Data collection is through online questionnaires. There are three sections questionnaire, demographic factors, financial literacy, and risk profile. The data processing techniques used are descriptive statistical analysis and multiple regressions. The results showed that bank employees in Bandung had financial literacy indexes categorized as "medium" or "sufficient" (66.7%) with a risk profile index of "moderate" type (60%). Demographic factors that affect financial literacy are age, education level, and organizational position. While the factor that affects the risk profile is age and gender. Research has also revealed a strong correlation between financial literacy and risk profile.